2013
DOI: 10.1016/j.ihj.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Reperfusion Therapy with Indigenous Tenecteplase in 15,222 patients with ST Elevation Myocardial Infarction – The Indian Registry

Abstract: This study confirms the safety and efficacy of indigenous tenecteplase in Indian patients with STEMI, including high risk subgroups. It also highlights the fact that delayed treatment denotes denial of benefits of pharmacologic reperfusion therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
1
3
0
11
Order By: Relevance
“…An outcome of death was higher in women, and this can be attributed to a higher proportion of diabetics and hypertensives in this subgroup. This scenario has also been observed in other studies when identifying that although the STEAMI incidence was lower in women, mortality is approximately twice as high (Iyengar et al 2013). It is also observed that the TIMI risk score for STEAMI is higher in women (Bagai et al 2014).…”
Section: Discussionsupporting
confidence: 84%
“…An outcome of death was higher in women, and this can be attributed to a higher proportion of diabetics and hypertensives in this subgroup. This scenario has also been observed in other studies when identifying that although the STEAMI incidence was lower in women, mortality is approximately twice as high (Iyengar et al 2013). It is also observed that the TIMI risk score for STEAMI is higher in women (Bagai et al 2014).…”
Section: Discussionsupporting
confidence: 84%
“…Iyengar et al analysed the efficacy and safety of tenecteplase in 15,222 patients with STEMI. 4 Overall, 95.43% of patients had clinically successful thrombolysis with higher success rate (96.54%) in patients treated within 3 hours, success rate of 85.38% in those presented in 6 hours. STREAM trial demonstrated that patients presented within 3 hours of symptoms onset and fibrinolysed had better outcome 5 (Shock, CHF or reinfarction upto 30 days).…”
Section: Discussionmentioning
confidence: 85%
“…Similar results were also observed in Indian registry, where more than 90% of CST was seen with tenecteplase including high risk subgroup. 4 In earlier studies, the incidence of diabetes in acute myocardial infarction is 10% -25%. In our study the prevalence was much higher, 49%.…”
Section: Discussionmentioning
confidence: 98%
“…Частота внутричерепных кровоиз-лияний -0,62%, серьёзных кровотечений -3,18%. Задержка с применением препарата более 6 часов от начала ангинозного приступа приводила к увели-чивающейся частоте развития сердечной недостаточ-ности, желудочковых тахиаритмий и в целом -более высокой смертности [16].…”
Section: активаторы плазминогена в неотложной терапии тромбозаunclassified